2012
DOI: 10.1166/jnn.2012.6269
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Method Simulation of the Molding Process for Thermal Nano-Imprint Lithography

Abstract: We made a numerical study on the deformation of a viscoelastic polymethyl methacrylene (PMMA) resist when a rigid SiO2 stamp with a rectangular line pattern is imprinted into the PMMA resist for thermal nano-imprint lithography (NIL). The stress distribution in the polymer resist during the molding process is calculated by a finite element method (FEM). Our simulation results reveal that the asymmetric von Mises stress is distributed over the polymer around the external line, which seems to be due to the squee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Lan et al (2009) analyzed the temperature and time dependence of polymer deformation by finite element analysis and predicted the pattern replication after thermal imprint process. Cho et al (2012) calculated the stress distribution in the polymer resist during the molding process and revealed that the asymmetric von Mises stress is distributed over the polymer substrate. Song et al (2008) studied the stress and deformation behavior in polymer resist during the cooling and de-molding process via finite element method.…”
Section: Introductionmentioning
confidence: 99%
“…Lan et al (2009) analyzed the temperature and time dependence of polymer deformation by finite element analysis and predicted the pattern replication after thermal imprint process. Cho et al (2012) calculated the stress distribution in the polymer resist during the molding process and revealed that the asymmetric von Mises stress is distributed over the polymer substrate. Song et al (2008) studied the stress and deformation behavior in polymer resist during the cooling and de-molding process via finite element method.…”
Section: Introductionmentioning
confidence: 99%